2020
DOI: 10.29109/gujsc.618229
|View full text |Cite
|
Sign up to set email alerts
|

Bakır ve Silisyum İlavelerinin Al-25Zn Alaşımının CVD Al2O3 Kaplamalı Takımlarla Tornalanmasında İşlenebilirliğe Etkisinin İncelenmesi

Abstract: In this study, Al-25Zn-3Cu and Al-25Zn-3Cu-3Si alloys were obtained by adding Copper (Cu) and Silicon (Si) to Al-25Zn alloy using induction melting and permanent mold casting method. Microstructural and mechanical properties of alloys were determined. The internal structure of Al-25Zn consisted of α and η phases, while the internal structure of Al-25Zn-3Cu consisted of α, α + η and θ phases. In addition to these phases, eutectic and primary silicon particles were observed in the internal structure of Al-25Zn-3… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
0
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
5

Relationship

3
2

Authors

Journals

citations
Cited by 5 publications
(3 citation statements)
references
References 37 publications
0
0
0
Order By: Relevance
“…5-7). This was thought to be due to the formation of more Mg2Si precipitates in the microstructure of the Al-7Si-0.6Mg alloy and the decreased in EF depending on the increase in Mg content [2,16] It was observed that the formation of BUL and BUE in cutting tools reduced with the increment in V. The tool/chip contact surface area decreased depending upon the increment in V. At the same time, high cutting temperatures occurred due to high V in Al-based alloys and plastic deformation of the chip was facilitated and BUL and BUE formation were reduced [29,30]. It was observed that the formation of BUL and BUE in the cutting tool increased with the increment in f. It was thought that this situation was caused by the high volume of metal removal rate that caused high c) d) pressure and CFs and the increase in the tool/chip interface contact area [31,32].…”
Section: Evaluation Of Machinability Propertiesmentioning
confidence: 98%
See 1 more Smart Citation
“…5-7). This was thought to be due to the formation of more Mg2Si precipitates in the microstructure of the Al-7Si-0.6Mg alloy and the decreased in EF depending on the increase in Mg content [2,16] It was observed that the formation of BUL and BUE in cutting tools reduced with the increment in V. The tool/chip contact surface area decreased depending upon the increment in V. At the same time, high cutting temperatures occurred due to high V in Al-based alloys and plastic deformation of the chip was facilitated and BUL and BUE formation were reduced [29,30]. It was observed that the formation of BUL and BUE in the cutting tool increased with the increment in f. It was thought that this situation was caused by the high volume of metal removal rate that caused high c) d) pressure and CFs and the increase in the tool/chip interface contact area [31,32].…”
Section: Evaluation Of Machinability Propertiesmentioning
confidence: 98%
“…5 and 6). The tool/chip interface temperature increased with the increment of V. Due to this temperature increment, the YS of the machined material reduced and the formation of plastic deformation became easier and the CF reduced [28,29]. It was thought that the CF increased due to the increment in the f parameter and the increase in the volume of chip removed in unit time during cutting and the power required for plastic deformation [2].…”
Section: Evaluation Of Machinability Propertiesmentioning
confidence: 99%
“…250 m/dak sabit kesme hızında ilerlemenin 0,05 mm/dev'den 0,25 mm/dev'e artması ile kesme kuvveti ve yüzey pürüzlülüğü sırasıyla %189,75 ve %119,08 oranında artarken, sabit 550 m/dak kesme hızında bu değerlerin sırasıyla %142,50 ve %567,24 oranında arttığı tespit edilmiştir.İlerlemenin artmasına bağlı olarak birim zamanda kaldırılması talaş hacminin artması kesme kuvvetini arttırmaktadır. Aynı zamanda ilerlemedeki bu artış, takım-talaş arayüzeyinde sürtünme yüzey alanının artmasına neden olarak kesme kuvvetini arttırdığı düşünülmektedir(Bayraktar & Demir, 2020; Bayraktar vd., 2020;Bayraktar & Çamkerten, 2020; Korkut & Dönertas, 2007). Şekil 3 ve 4'teki grafikler incelendiğinde en düşük kesme kuvveti ve yüzey pürüzlülüğü değerlerinin testler kapsamında kullanılan en yüksek kesme hızı (550 m/dak) ve en düşük ilerleme değerlerinde (0,05 mm/dev) ölçüldüğü tespit edilmiştir.Şekil 4.…”
unclassified